Digital citizenship skills among undergraduate students in Malaysia: A preliminary study - Noor Banu Mahadir; Nur Hidayah Baharudin; Nurul Nadia Ibrahim (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of the study was to examine level of digital citizenship skills among undergraduate students at the Sultan Idris Education University, Perak, Malaysia. The study focused on three sub-variables of digital citizenship skills; online wellbeing, online learning and online safety. The paper present report from a questionnaire conducted on 1000 students from nine different faculties. Items for each variable were constructed based on literature highlights related to digital citizenship framework and through experts’ validation. A descriptive statistic was used in determined the level of digital citizenship skills among the undergraduate students. The findings of the study showed that the level of digital citizenship skills of students is at a high level. This study expected to help stakeholders to further emphasize the study of digital citizenship and digital citizenship education in Malaysia in more detail.